Preparação e propriedades de uma argila paranaense pilarizada com polihidroxications de alumínio - Pergher, Sibele Berenice Castellã (1993)
Montmorillonite clay from São Mateus do Sul (Brazil), provided by PETROSIX, was pillared with aluminium polyhydroxications. The solution to carry out this pillarization was prepared by adding NaOH (0,2M) slowly into AlCl3 (0,2 M) under strong agitation at 25°C until the molar ratio OH/Al equals 2. Sample of this solution were taken and aged 1 hour, 6 and 15 days. These samples were added into dry clay and clay suspensions containing 1g/15 ml of water and 1g/100 ml of water, keeping the ratio of 15 meq of Al per gram of dry clay. The formed suspensions were kept under agitation at 25°C for 2 hours and after filtered and washed. The washing was carried out with deionized water and in some cases with ethanol. The solid material was dryed either under room temperature or by liofilization. The solid materials were finally calcinated at 400°C to obtain the pillared clays. The following techniques were used to characterise the pillared clays: chemical analysis, XRD, DSC, TGA, N2 adsorption and eletronic. Pillared clays were also tested in cumene and triisopropylbenzene cracking reactions at 400°C. Results demonstrated that the pilllarization process increases the basal spaces of the natural clay from 10 Å (anidrous form) to 18 Å Pillarization process increases the superficial area measured by BET from 45 to 300 m2/g. After pillarization the volume of micropouros was increased 12 times and the volume of mesoporous reduced to its half. The washing process affects the form of particles agregates. Washing made with ethanol results in less agglomerates of particles. The two drying processes resulted in very similar products. The deslamination of pillared material did not occurred. Pillared clays maintained its structure expanded until temperatures of 700°C, presenting d001= 17,6 Å and BET superficial area of 300 m2/g. The decreasing of the concentration of clay in the suspensions leads to products with larger basal spaces, higher quantity of embodied aluminum and more catalytic properties. Clay materials prepared with oligomeric solution aged for 1 hour presented smaller basal spaces and smaller superficial area measured by BET, higher quantity of embodied aluminum and catalytic properties. The cumene cracking reaction occurs only with pillared material. The triisopropylbenzene cracking reaction occurs partially in the natural clay with moderated conversions and the total cracking occurs only in pillared materials. Deactivation of pillared clays in both reactions are fast.